Mermelada de noni (Morinda citrifolia) con adición de maracuyá (Passiflora edulis) como saborizante natural - Benavides Sotomayor, Erika Virginia (2013)
The present investigation was carried out at the Experimental Farm "The Mary" of the State Technical University Quevedo, in the Laboratory of Food Science of the Faculty of Animal Science, located in the km 7 track Quevedo - The Splice, in the Province of the Rivers. The objectives were the following: Perform analysis physical, chemical and microbiological tests of the marmalade; determine the level of concentration that improve the organoleptic quality of the marmalade; establish the benefit cost ratio (B/C We applied a completely randomized design with four treatments and four replications were used two types of fruit (noni and maracuya) with different levels of concentration. For the comparison between means were used the Tukey test (p ≤ 0.05 ). In the variables of pH there was no statistically significant difference by issuing securities between 3.47-3.55 in pH, in contrast with the other variables showed values of 61,25 – 63,5 brix, 1,3 -1,77 per cent in acidity. In relation to the organoleptic analysis the jams presented; smell of noni much and maracuya quite, quite to noni flavor and moderate maracuya, lightweight to acid, quite to cinnamon color and in taste quite sweet and moderate acid, also evaluating the overall appearance the tasters were determined that the best treatment was (70% of noni + 30% maracuya).